2021
DOI: 10.3390/molecules26113367
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Antimicrobial and Antioxidant Activities of Plant Essential Oils and Extracts as Candidate Ingredients for Edible Coatings to Control Decay in ‘Wonderful’ Pomegranate

Abstract: This study determined the antimicrobial and antioxidant activity of lemongrass (LO), thyme (TO), and oregano (OO) essential oils and ethanolic extracts of pomegranate peel (PPE) and grape pomace (GPE) as candidate ingredients for edible coatings. Antifungal effects against Botrytis cinerea and Penicillium spp. were tested using paper disc and well diffusion methods. Radical scavenging activity (RSA) was evaluated using 2,2-diphenyl-1-picrylhydrazyl and 2,2′-azinobis-3-ethylbenzothiazoline-6-sulfonic acid assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 87 publications
2
7
1
Order By: Relevance
“…The resistance to decay incidence and internal decay exhibited by ‘Wonderful’ pomegranates coated with GA + LM and GA + PP corroborates with recent studies which have proven the antimicrobial activities against postharvest pathogens of either LM or PP alone and when combined with coatings [ 60 , 96 ]. In this present study, internal decay observed was due to grey mold ( Botrytis cinerea ) and blue mold ( Penicillium spp.)…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The resistance to decay incidence and internal decay exhibited by ‘Wonderful’ pomegranates coated with GA + LM and GA + PP corroborates with recent studies which have proven the antimicrobial activities against postharvest pathogens of either LM or PP alone and when combined with coatings [ 60 , 96 ]. In this present study, internal decay observed was due to grey mold ( Botrytis cinerea ) and blue mold ( Penicillium spp.)…”
Section: Discussionsupporting
confidence: 85%
“…Studies have shown that the application of edible coatings on pomegranate fruit stored under low temperature conditions suppressed decay weight loss and maintained overall quality [ 58 , 59 ]. Similarly, Kawhena et al [ 60 , 61 ] demonstrated the efficacy gum arabic, sodium alginate and starch-based coatings to minimize weight loss and decay severity in ‘Wonderful’ pomegranates during cold storage and shelf life. However, to the best of our knowledge, few reports exist which show the effect of coatings enriched with active components such PP and/or LM on postharvest quality of any pomegranate fruit during storage and shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in Tv, thymol was the main component (22.71%), followed by p-cymene and γ-terpinene. Thymol is an isomer of carvacrol, with differences in the hydroxyl group position [11]. Studies have reported that the antifungal activity of thymol and carvacrol was related to the hydroxyl group position and the species of fungus.…”
Section: Discussionmentioning
confidence: 99%
“…All three compounds are monoterpenes with hydroponic and lipophilic characteristics, making it easy to attach to the membrane's hydrophobic region and dissolve in the phospholipid bilayer, leading to fungal death [8]. In carvacrol and thymol, the phenolic hydroxyl groups might have damaged the cell membrane by oxidative phosphorylation uncoupling, which contributed to the higher antifungal activities of Tv and Oh [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation